CFD-DEM characterization and population balance modelling of a dispersive mixing process. (12th October 2022) - Frungieri, Graziano; Boccardo, Gianluca; Buffo, Antonio; Karimi–Varzaneh, Hossein Ali; Vanni, Marco
Highlights: A numerical method to study dispersive mixing in an internal mixer is presented. CFD simulations are used to compute the flow field in an internal mixer. A discrete element method based on Stokesian dynamics is used to predict breakup. Agglomerate breakup data are used to tune a population balance model. Abstract: This work investigates the breakup dynamics of solid agglomerates in a polymer compounding operation, by using computational fluid dynamics (CFD) simulations together with discrete element method (DEM) simulations. CFD simulations are used to compute the flow field and the shear stress distribution inside a 2D section of a typical internal mixer for polymer compounding. DEM simulations are instead used to predict the mechanical response of the agglomerates and to detect the critical viscous shear stress needed to induce breakup. DEM breakup data and viscous stress distributions are correlated by a first–time passage–statistics and used to calibrate a population balance model. The work returned detailed insights into the flow field characteristics and into the dispersive mixing kinetics. The simulation strategy herein reported can be adapted to study generic solid–liquid disperse flows in which the breakup of the solid phase is found at the core of the system behaviour.